Seroprevalence and risk factors associated with Helicobacter pylori infection among children aged less than 18 years old in Duhok Province, Iraq: Prevalence and risk factors for H. pylori infection - Al-Brefkani, Azad Mohammed Taher; Naqid, Ibrahim A; Yahya, Nizar Bakir; Hussein, Nawfal (Journal of Contemporary Medical Sciences, 2021)
Objectives: Helicobacter pylori infection is predominantly acquired in early childhood and persists for decades before causing disease. This study aimed to detect the prevalence of H. pylori infection and identify potential factors associated with infection in Duhok province, Iraq. Methods: This cross-sectional study was conducted in Duhok Province, Kurdistan Region, Iraq. Over a four-year period from 2016 to 2020, a total of 381 children aged four to 18 years who attended the hospitals and were evaluated for specific IgG antibodies against H. pylori using serological tests were included. A questionnaire was completed at the start of the study. H. pylori serology data were analyzed using the chi-square test. Results: The seroprevalence of H. pylori IgG-specific antibodies among the study participants was 31%. The infection rate significantly increased with increasing age of the participants (p<0.001), from 19.8% among four to five-year-olds to 42.9% among 16 and 18-year-olds. The infection rate was significantly higher in girls (35.9%) than that in boys (26.5%) (p<0.047). Infections were also higher among university students (41%; p<0.001), children from the country-side population (41%; p<0.001), children from crowded households (67.3%; p<0.001), and children with a history of gastrointestinal pain (44.4%; p>0.001). Conclusion. The prevalence rate of H. pylori infection among children in Duhok province is quite similar to that reported in previous studies in the Kurdistan region, Iraq, and increases with age. University attendance, history of gastrointestinal pain, countryside population, and overcrowding were risk factors associated with H. pylori infection. Valuable approaches to improve sanitary purposes and educational and socioeconomic status should be emphasized and promoted to reduce the risk of H. pylori infection among children.